Profile, objectives, competences and future professional prospects of the students of the Degree in Industrial Design and Product Development Engineering at the University of Zaragoza - Ana Serrano Tierz; A. M. Biedermann; J.L. Santolaya Sáenz (Universitat Politècnica de València, 2016)
This  paper  aims  at  knowing  students profile,  analyzing  the training,  personal and professional prospects of students in Degree in Industrial Design and Product Development Engineering at the University of Zaragoza. It is a fairly new degree, within the branch of Engineering, pioneer in the introduction of Grades, and that currently counts  with  a  high  degree  of  access applications by students.Given the current situation of social change and educational framework, we want to know what the goals of students are and to what extent they are fulfilled; what perception students have regarding the acquisition of the developed competences and  the  competences  required  by companies; which abilities are necessary for their teachers and in which degree they are present and, eventually, what are the future professional prospects for the students in an uncertain environment.For this purpose, a survey, based on a number of questions, has been conducted including a representative sample of 242 students in all the years of the Grade. The  results  have  been  structured  into three  sections  that  analyze  the  basic characteristics of students, whose career choice  is  vocational;  perception  of  the development of the competences within which the ability to generate new ideas and the ability to work under pressure are highlighted, and career prospects. The study shows that the professional future is highlighted within the training prospects of students, who perceive that the level of competences required in the Grade match the demands of the companies.